Zur Kritik von Christoph Bruns an Dogma im Wandel - Seewald, Michael (Theologie und Philosophie, 2020)
This article is a response to Christoph Bruns’s criticism of the book Dogma im Wandel: Wie Glaubenslehren sich entwickeln (Freiburg 2018) by Michael Seewald. The article addresses three issues discussed by Bruns: the role of the magisterium of the pope and the college of bishops, the controversial question of the level of what is binding in the secondary realm of doctrine, and Bruns’s conception of a homogeneous development of doctrine.